2020
DOI: 10.1186/s12934-020-01386-1
|View full text |Cite
|
Sign up to set email alerts
|

A glucotolerant β-glucosidase from the fungus Talaromyces amestolkiae and its conversion into a glycosynthase for glycosylation of phenolic compounds

Abstract: Background The interest for finding novel β-glucosidases that can improve the yields to produce second-generation (2G) biofuels is still very high. One of the most desired features for these enzymes is glucose tolerance, which enables their optimal activity under high-glucose concentrations. Besides, there is an additional focus of attention on finding novel enzymatic alternatives for glycoside synthesis, for which a mutated version of glycosidases, named glycosynthases, has gained much interes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…Its beneficial and harmful effects on humans have been well documented. Enzymes and pigments produced by some species of the genus are of industrial importance, such as β-glucosidase produced by T. amestolkiae N. Yilmaz et al [ 1 ] and T. cellulolyticus T. Fujii et al [ 2 ], and red pigments by T. atroroseus N. Yilmaz et al [ 3 , 4 ]. Talaromycosis caused by several species were also reported [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its beneficial and harmful effects on humans have been well documented. Enzymes and pigments produced by some species of the genus are of industrial importance, such as β-glucosidase produced by T. amestolkiae N. Yilmaz et al [ 1 ] and T. cellulolyticus T. Fujii et al [ 2 ], and red pigments by T. atroroseus N. Yilmaz et al [ 3 , 4 ]. Talaromycosis caused by several species were also reported [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…BGL-1 is a monomeric protein, with the lowest molecular mass among the three BGLs studied. The extracellular activity secreted in P. pastoris was outstanding (75 U/mL), indicating the overexpression of bgl1 in this system (Méndez-Líter et al 2020). The monomeric units of BGL-2 and 3 have similar molecular mass, but BGL-3 showed to be a dimer when analyzed under non-denaturing conditions (Méndez-Líter et al 2017.…”
Section: β-Glucosidases From T Amestolkiae: Enzymes With Unique Characteristicsmentioning
confidence: 88%
“…The assessment of the activity of the three BGLs on cellooligosacharides from 2 to 6 glucose units confirmed that they all acted on cellobiose and their efficiency varied with the chain length (Table 3). Despite the low hydrolytic efficiency of BGL-1 on the substrates assayed (Table 3), this enzyme showed an outstanding glucotolerance, and its inhibition constant against glucose (Ki = 3.78 M) is among the highest described to date (Méndez-Líter et al 2020). This work also revealed that BGL-1 is a versatile enzyme, since it had higher hydrolytic activity on sophorose (β-1,2 disaccharide of glucose) than on cellobiose (β-1,4 disaccharide of glucose).…”
Section: β-Glucosidases From T Amestolkiae: Enzymes With Unique Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Protein engineering enabled the production of the β-1,2 transglycosylating BGL-1-E521G that was able to utilise phenolic acceptors such as epigallocatechin gallate (EGCC) in addition to pNP-sugars, whilst using α-glucosyl-fluoride as the donor. Consequently a variety of β-1,2-glucosylated phenolic compounds were produced in a regioselective manner [ 70 ].…”
Section: Glycoside Hydrolasesmentioning
confidence: 99%